Magnetothermopower in A2−xLaxFeMoO6 (A = Sr, Ba) - G. V. M. Williams; J. Stephen (Advances in Condensed Matter Physics)
A magnetothermopower has been observed in electronically spin-polarized polycrystalline Sr2-xLaxFeMoO6 and Ba2FeMoO6. The magnetothermopower is linear up to ~50 K for Sr2-xLaxFeMoO6 and linear up to ~270 K for Ba2FeMoO6. We suggest that the magnetothermopower may arise from a spin-tunneling magnetothermopower between the grains.